Functional Kimchi Beverage Enhanced with γ-Aminobutyric Acid (GABA) Through Serial Co-Fermentation Using Leuconostoc citreum S5 and Lactiplantibacillus plantarum KS2020 - Min-Jeong Kwon; Ji-Eun Kim; Sam-Pin Lee (Fermentation)
A plant-based beverage enhanced with GABA was developed through serial co-fermentation using Leuconostoc citreum S5 and Lactiplantibacillus plantarum KS2020. The first lactic acid fermentation was performed by Leu. citreum S5 with a vegetable mixture consisting of sliced radish, ginger, garlic, red pepper, bell pepper, and sucrose. The viable cell count of Leu. citreum S5 increased to 9.11–9.42 log CFU/mL with higher sucrose contents, indicating the highest value of 9.42 log CFU/mL at 5% sucrose on day 1. Mannitol and dextran production levels in the first fermented vegetable mixture were 6.66–14.54 mg/mL and 0.44–2.26%, respectively. A higher sucrose content produced more dextran, resulting in a concomitant increase in viscosity of 49.4 mPa·s. The second co-fermentation for the kimchi beverage base was performed by Lb. plantarum KS2020 for 5 days, resulting in 8.22–9.60 log CFU/mL. The pH of the co-fermented kimchi beverage base increased to 6.19–9.57 with an increasing monosodium glutamate (MSG) content (3–7%), while titratable acidity significantly decreased to 0.0–0.8%. The final co-fermented kimchi beverage base was enriched with 2.6% GABA. Consequently, a GABA kimchi beverage base with probiotics, a red pigment, and a pleasant flavor was developed using only vegetable ingredients by serial co-fermentation using lactic acid bacteria.